1982
DOI: 10.1080/03079458208436113
|View full text |Cite
|
Sign up to set email alerts
|

Experimental trichothecene mycotoxicosis produced in broiler chickens byFusarium sporotrichiellavar.sporotrichioides

Abstract: SUMMARYFusarium sporotrichiella var. sporotrichioides (Bilay), cultured on . sterilised popcorn at 23°C and then at 8°C, 16°C and 23°C and fed as 50% of the diet, was lethal to 7-day-old male broiler chickens. The 8°C culture, containing T-2 toxin at 50 parts per million (ppm) and neosolaniol at 5 ppm, was given as whole culture at dietary concentrations of 10%, 5%, 1% and 0% for 17 days and 1% for 42 days. Half the chickens that were fed the 10% diet died during the 17 days (5 ppm T-2 toxin and 0.5 ppm neosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
(11 reference statements)
1
12
0
Order By: Relevance
“…These findings were not reported for gizzard lesions produced by feeding diets containing fish meal, 16 high levels of histamine, 14 copper, 9,17 or mycotoxins. 15,23 Therefore, these findings may be available for presumptive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were not reported for gizzard lesions produced by feeding diets containing fish meal, 16 high levels of histamine, 14 copper, 9,17 or mycotoxins. 15,23 Therefore, these findings may be available for presumptive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…15 Gizzard erosions also have been observed at a high rate in the embryos and chicks of broilers. 36 However, several natural cases of gizzard erosion associated with FAV infection have been reported in layer chickens, broiler chickens, and quails in recent years.…”
mentioning
confidence: 90%
“…Sporadically there are egg spots with frequency up to about 3%. This was confirmed by Hoerr et al (1982) who found that this toxin causes severe lesions in the mouth, salivary glands and tongue where a yellowish pseudomembranes are formed and after there removal lesions remain.…”
Section: Chickensmentioning
confidence: 68%
“…The levels of ΖΕΑ in some examined samples may be of concern, but it is unlikely that the individual levels of the other toxins detected would be harmful to either animal or human health (Agnew et al 1986). However, the presence of more than one mycotoxin in the majority of the samples could perhaps be of extra significance because of the reported synergistic and/or additive action of these mycotoxins (Hoerr et al 1982).…”
Section: Discussionmentioning
confidence: 99%